2009
DOI: 10.1103/physrevb.79.155449
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb explosion as a probe to understand the mechanism of electron stripping from ions interacting with crystalline solids

Abstract: When an ion impinges on a solid, it rapidly undergoes a process in which its electrons are stripped away provided the velocity of the orbiting electrons is smaller than the projectile speed. Electron stripping determines any posterior behavior of the ions in the solid, and it is assumed that it takes place on the surface of the solid, but no information is available on the details of the process. Here we show, using the Coulomb explosion of C 2 + ions moving in Si as a tool, that electron stripping takes place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…This range of energies is particularly suitable for the ion accelerator at CMAM (Fig. 3a) and, thus, there is an extensive collection of studies on this topic: the magnetic properties of graphite [32], the e↵ect of Coulomb explosion for molecular ions [33], the amorphization, structural changes and the optical properties of LiNbO 3 [34][35][36][37] and SiO 2 [38][39][40], the influence of an external magnetic field on the damage in Fe 90 Cr 10 [41] and Fe 85 Cr 15 alloys [42], the ion-induced elongation of Ag nanoparticles embedded in silica [43], and the improvement in electrical conductivity of LiTaO 3 and LiNbO 3 crystals [44]. The scientific and technological interest of diamond has been also a point of attention for the researchers at CMAM.…”
Section: High-energy Heavy Ionsmentioning
confidence: 99%
“…This range of energies is particularly suitable for the ion accelerator at CMAM (Fig. 3a) and, thus, there is an extensive collection of studies on this topic: the magnetic properties of graphite [32], the e↵ect of Coulomb explosion for molecular ions [33], the amorphization, structural changes and the optical properties of LiNbO 3 [34][35][36][37] and SiO 2 [38][39][40], the influence of an external magnetic field on the damage in Fe 90 Cr 10 [41] and Fe 85 Cr 15 alloys [42], the ion-induced elongation of Ag nanoparticles embedded in silica [43], and the improvement in electrical conductivity of LiTaO 3 and LiNbO 3 crystals [44]. The scientific and technological interest of diamond has been also a point of attention for the researchers at CMAM.…”
Section: High-energy Heavy Ionsmentioning
confidence: 99%
“…[5,9,[23][24][25][26] In Ref. [27], the Rutherford backscattering energy spectrum of carbon fragments which were generated by a 1.847 MeV C + 2 cluster beam interacting with a silicon crystal target was used to measure the time when the Coulomb explosion just happened. It was reported that the electron stripping time was around 0.1 fs for T 100 spatial period, 0.12 fs for T 211 spatial period, and 0.2 fs for T 111 spatial period.…”
Section: Introductionmentioning
confidence: 99%